2017
DOI: 10.1007/s00256-017-2695-5
|View full text |Cite
|
Sign up to set email alerts
|

MRI characteristics of torn and untorn post-operative menisci

Abstract: Objective To compare magnetic resonance imaging (MRI) characteristics of torn and untorn post-operative menisci. Methods The study group consisted of 140 patients with 148 partially resected menisci who were evaluated with a repeat knee MRI examination and subsequent repeat arthroscopic knee surgery. Two musculoskeletal radiologists retrospectively assessed the following MRI characteristics of the post-operative meniscus: contour (smooth or irregular), T2 line through meniscus (no line, intermediate signal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 20 publications
(25 reference statements)
1
21
0
Order By: Relevance
“…The most useful MRI characteristics to predict torn postoperative menisci at surgery were a change in the signal pattern through the meniscus compared with baseline MRI and a displaced meniscal fragment followed by a high T2 line through the meniscus, an intermediate to high T2 line through the meniscus, and an irregular meniscal contour. 20 On the basis of these MRI characteristics, Kijowski et al 20 reported 64 meniscal retears (42.25%) among 148 patients.…”
Section: Discussionmentioning
confidence: 99%
“…The most useful MRI characteristics to predict torn postoperative menisci at surgery were a change in the signal pattern through the meniscus compared with baseline MRI and a displaced meniscal fragment followed by a high T2 line through the meniscus, an intermediate to high T2 line through the meniscus, and an irregular meniscal contour. 20 On the basis of these MRI characteristics, Kijowski et al 20 reported 64 meniscal retears (42.25%) among 148 patients.…”
Section: Discussionmentioning
confidence: 99%
“…15 MRI signals at the repair site were assessed on T2-weighted images using the signal characteristics of the grading systems of Kijowski et al. 16 and Crues et al. 17 Degenerative changes on weight-bearing plain radiographs were graded using the Kellgren-Lawrence grading system.…”
Section: Methodsmentioning
confidence: 99%
“…The absence of a fluid-like signal at the site of repair on proton density or T2-weighted images was considered to indicate a healed meniscus. 16 , 17 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, MRI is the preferred imaging modality for assessing patients with persistent or recurrent symptoms after meniscal surgery and may be performed conventionally or with an intra-articular contrast agent. 5 42 43 44 45…”
Section: Meniscimentioning
confidence: 99%